A new species of Ashlockobius (Heteroptera: Rhyparochromidae: Myodochini) from Venezuela - Dellapé, Pablo Matías (Zootaxa, 2003)
A new species of Ashlockobius Slater & Slater 1999 (Heteroptera: Rhyparochromidae: Myodochini) is described from Venezuela, the male genitalia are illustrated, and the presence of a stridulatory mechanism is discussed.